Alternative splicing generates HER2 isoform diversity underlying antibody–drug conjugate resistance in breast cancer - Guardia, Gabriela D.A.; dos Anjos, Carlos H.; Rangel-Pozzo, Aline; dos Santos, Filipe F.; Birbrair, Alexander; Asprino, Paula F.; Camargo, Anamaria A.; Galante, Pedro A.F.

(untitled) (Genome Research, 2025)
Breast cancer (BC) is a heterogeneous disease that can be molecularly classified based on the expression of the ERBB2 receptor (also known as HER2) and hormone receptors. Targeted therapies for HER2-positive BC, such as trastuzumab, antibody–drug conjugates (ADCs) and tyrosine kinase inhibitors, have improved patient outcomes, but primary/acquired resistance still poses challenges that can limit treatments’ long-term efficacy. Addressing these obstacles is vital for enhancing therapeutic strategies and patient care. Alternative splicing, a post-transcriptional mechanism that enhances transcript diversity (isoforms), can produce proteins with varied functions, cellular localizations, or binding properties. Here, we comprehensively characterize the HER2 alternative splicing isoforms, assess their expression in primary BC patients and cell lines, and explore their role in resistance to anti-HER2 therapies. We expand the catalog of known HER2 protein-coding isoforms from 13 to 90, revealing distinct patterns of protein domains, cellular localizations, and protein structures, along with their antibody-binding sites. By profiling expression in 561 primary BC samples and mass spectrometry data, we discover a complex landscape of HER2 isoform, revealing novel transcripts that were previously unrecognized and are not assessed in routine clinical practice. Finally, the assessment of HER2 isoform expression in BC cell cultures sensitive or resistant to trastuzumab and ADCs reveals that drug-resistant cells shift their expression toward isoforms lacking antibody-binding domains. Our results broaden the understanding of HER2 isoforms, revealing distinct mechanisms of potential resistance to anti-HER2 therapies, particularly ADCs. This expanded landscape of HER2 isoforms emphasizes the crucial role of alternative splicing investigations in advancing precision-targeted cancer therapies.